Sleep and Wakefulness Are Controlled by Ventral Medial Midbrain/Pons GABAergic Neurons in Mice - Takata, Yohko (J Neurosci, 2018)
Sleep–wake behavior is controlled by a wide range of neuronal populations in the mammalian brain. Although the ventral midbrain/pons (VMP) area is suggested to participate in sleep–wake regulation, the neuronal mechanisms have remained unclear. Here, we found that nonspecific cell ablation or selective ablation of GABAergic neurons by expressing diphtheria toxin fragment A in the VMP in male mice induced a large increase in wakefulness that lasted at least 4 weeks. In contrast, selective ablation of dopaminergic neurons in the VMP had little effect on wakefulness. Chemogenetic inhibition of VMP GABAergic neurons also markedly increased wakefulness. The wake-promoting effect of the VMP GABAergic neuron ablation or inhibition was attenuated to varying degrees by the administration of dopamine D1 or D2/3 receptor antagonists and abolished by the administration of both antagonists together. In contrast, chemogenetic activation of VMP GABAergic neurons very strongly increased slow-wave sleep and reduced wakefulness. These findings suggest that VMP GABAergic neurons regulate dopaminergic actions in the sleep–wake behavior of mice. SIGNIFICANCE STATEMENT Current understanding of the neuronal mechanisms and populations that regulate sleep–wake behavior is incomplete. Here, we identified a GABAergic ventral midbrain/pons area that is necessary for controlling the daily amount of sleep and wakefulness in mice. We also found that these inhibitory neurons control wakefulness by suppressing dopaminergic systems. Surprisingly, activation of these neurons strongly induced slow-wave sleep while suppressing wakefulness. Our study reveals a new brain mechanism critical for sleep–wake regulation.